Comparative evaluation of titanium-prepared platelet-rich fibrin with and without herbal extract: A histological study - Gummaluri Shiva Shankar; Gurumoorthy Kaarthikeyan; Damera Trinath Kishore; Boddeda Anusha; Kodem Tejaswi; Lekkala Sivaram (Vojnosanitetski Pregled)
Background/Aim. Injecting herbal extract into platelet concentrates is one of the newer treatment protocols, which enables platelet concentrates to act as sustained drug delivery (DD) systems. Histological analysis of titanium-prepared platelet-rich fibrin (T-PRF) injected with herbal extract, could help assess the appearance (pattern) and structural changes of T-PRF. The aim of the study was to evaluate the appearance of the fibrin network, cellularity, and fibrin border area of T-PRF alone and T-PRF injected with herbal extract. Methods. A total of 40 histological slides were prepared from 10 mL of blood from each patient, 20 with T-PRF alone and 20 with T-PRF+herbal extract. The slides were divided into a group consisting of T-PRF injected with neem gel (test group) and a group consisting of T-PRF alone (control group). The preparation protocol was made according to Bank-roft’s manual adapted for light microscopy. Results. Regarding the fibrin network features (dense vs. loose), no statistical significance was found among the studied groups (p = 0.172). A statistically significant difference was shown in the packeting (p = 0.018) and layered (p = 0.028) patterns of the fibrin network, and there was no statistically significant difference in the scattered (p = 0.749) pattern among the examined groups. Cellularity and cell pattern values were not statistically significantly different for both groups (p = 1.00, p = 0.3111, respectively). Moreover, the values determined for red blood cells, white blood cells, and platelets were not statistically significantly different (p = 0.147), as well as for the fibrin border area between cells and meshwork (p = 0.206). Conclusion. The obtained results could be useful for the development of a new treatment strategy in dentistry, by utilizing T-PRF with incorporated herbal extracts or antibiotics, as a local sustained DD system.